2016
DOI: 10.1016/j.cub.2016.01.067
|View full text |Cite
|
Sign up to set email alerts
|

A Neural Basis for Control of Cichlid Female Reproductive Behavior by Prostaglandin F 2α

Abstract: Summary In most species, females time reproduction to coincide with fertility. Thus, identifying factors that signal fertility to the brain can provide access to neural circuits that control sexual behaviors. In vertebrates, levels of key signaling molecules rise at the time of fertility to prime the brain for reproductive behavior [1–11], but how and where they regulate neural circuits is not known [12, 13]. Specifically, 17α,20β-dihydroxyprogesterone (DHP) and prostaglandin F2α (PGF2α) levels rise in teleost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 40 publications
1
73
0
Order By: Relevance
“…Beach, 1976;McCarthy et al, 1986). Juntti et al (2016) showed that, within minutes of prostaglandin F 2α (PGF 2α ) injection, female A. burtoni showed a naturalistic pattern of sexual behavior, as had been shown in other teleosts previously (Stacey, 1976;Cole and Stacey, 1984;Villars et al, 1985;Liley and Tan, 1985;Kidd et al, 2013) (Fig. 10).…”
Section: Neural Control Of Female Reproductive Behaviorsupporting
confidence: 54%
See 2 more Smart Citations
“…Beach, 1976;McCarthy et al, 1986). Juntti et al (2016) showed that, within minutes of prostaglandin F 2α (PGF 2α ) injection, female A. burtoni showed a naturalistic pattern of sexual behavior, as had been shown in other teleosts previously (Stacey, 1976;Cole and Stacey, 1984;Villars et al, 1985;Liley and Tan, 1985;Kidd et al, 2013) (Fig. 10).…”
Section: Neural Control Of Female Reproductive Behaviorsupporting
confidence: 54%
“…Astatotilapia burtoni is a unique species for understanding the role of social cognition in the evolution of social behavior because: (i) the social system is organized around resource guarding within small colonies of animals, a context that we can simulate well in a laboratory setting (Fernald and Hirata, 1977a,b;Fernald, 1977); (ii) male status is evident to observers because of their bright body color patterns and a lachrymal (eyebar) stripe, so behavior as a function of status is readily quantifiable (see Fig. 1); (iii) the neural systems responsible for social behavior include regulation of gonadotropin releasing hormone 1 (GnRH1)-containing neurons, which, in most species, ultimately controls reproduction -in A. burtoni, the size and connectivity of these neurons are regulated by male social status; (iv) levels of circulating hormones, tissue-specific peptides and DNA expression can be readily measured; and (v) the A. burtoni genome has been sequenced (Brawand et al, 2014), allowing us to measure gene expression in response to social situations (Desjardins et al, 2010), generate transgenic animals (Ma et al, 2015) and use CRISPR to delete key genes (Juntti et al, 2016).…”
Section: Model Social Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In any case, A. burtoni should serve as an excellent model for understanding the outcomes of polygenic sex determination for primary and secondary sexual characteristics. The availability of genome editing tools in the species permits mechanistic dissection of genetic variation [84, 85], while decades of research in the species provides a wealth of information regarding sexually dimorphic behavior, physiology, and related gene expression [38, 81, 8689]. …”
Section: Resultsmentioning
confidence: 99%
“…These and many other examples suggest that the biological systems modulating social behavior exhibit functional plasticity across developmental, seasonal, and rapid neuromodulatory timescales in a species-specific fashion. Investigations in alternative species systems have discovered novel mechanisms regulating several forms of social behavioral plasticity at different timescales (Ament et al, 2008; Ben-Shahar, 2005; Carpenter et al, 2014; Juntti et al, 2016; Maruska et al, 2013). For example, Juntti et al recently combined CRISPR/Cas9 and hormonal manipulations to demonstrate the causal role of prostaglandin F2α in modulating the rapid expression of female mating behaviors in Astatotilapia burtoni cichlid fish (Juntti et al, 2016).…”
Section: Patterns Of Social Behavioral Variation In Naturementioning
confidence: 99%